Perancangan Website Audit Energi pada Hotel Menggunakan Bahasa Pemrograman PHP - Fauzi, Muhammad Imam; Karnoto, Karnoto; Somantri, Maman (Transmisi, 2010)
Hotel is the commercial sector with a large energy needs. The rapid developments of hotel sector triggers an increase in energy demand for hotel. The role of conventional energy audits are found to be not sufficient in making efficient in energy use. Therefore, it is necessary to develop methods of energy audits using the website and it is connected by network so that the audit process can be done easier, faster, cheaper, and for a wide range area.This final project made a website of energy audit with a PHP programs. The website will be used to facilitate the audit process by performing data processing. The result, overall outcome data from various hotels can be displayed and yield detailed reports for each sector for each hotel. Page report programmed with the formulation and limitations based on applicable standards parameters of the intended reference. Database processing is done through MySQL database with database administration management through EMS SQL Manager 2005. Energy audit website as the result of this final project can shorten and simplify the energy audits process. In addition, this will be a cheaper method for energy audit process than conventional audit  methods. The analyzes report  as the results of audits  can be printed / used anytime and anywhere by the relevant agencies. The number of hotels that can be audited can be more than 2 hotels, depending on the ability of the system that supports it. Keyword :   audit, energy, program, and hotel.